Pengaruh video pendek terhadap tingkat pengetahuan masyarakat pada pertolongan CPR di Dusun Krajan Desa Karangbayat - Pramundari, Nanda Cecilia; Ekaprasetia, Feri; Susilo, Arief Judi (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
Limited public knowledge regarding Cardiopulmonary Resuscitation (CPR) necessitates the development of effective and easily accessible educational methods. Short videos have emerged as a promising medium to enhance this understanding. Consequently, a study was conducted to determine the effectiveness of a short video intervention on CPR knowledge among the residents of Karangbayat Village. The study employed a quasi-experimental one-group pretest-posttest design involving 32 randomly selected participants. Knowledge was assessed using a validated questionnaire before and after the intervention, with the data subsequently analyzed using the Wilcoxon signed-rank test. The results revealed a significant improvement in knowledge. At baseline, the majority of participants (65.6%) had knowledge classified as 'poor'. However, following the video intervention, the proportion of participants with 'sufficient' knowledge surged dramatically to 97%, increasing from 11 to 31 individuals. This difference was proven to be statistically significant (p = .001). These findings demonstrate that short videos are a highly effective medium for CPR education. This tool can serve as an accessible and impactful alternative to enhance community preparedness for handling medical emergencies. Therefore, the widespread implementation of such media is highly recommended to bolster public life-saving skills